2011
DOI: 10.1002/nau.21179
|View full text |Cite
|
Sign up to set email alerts
|

A galenical of traditional chinese herbal mixture (THC‐002) reduces expression of tachykinin peptides within urethras of spontaneously hypertensive rats

Abstract: Aging and saline-loading increased the expression of urethral tachykinin mRNAs and peptides. THC-002 partially decreased them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Previously, our studies indicated two major findings. One is that THC‐002 could inhibit C‐fiber sensory neurological pathway‐related neurotransmitters 12, 13. The other is that the cold stress‐induced detrusor overactivity is associated with activation of C‐fiber sensory nerves 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, our studies indicated two major findings. One is that THC‐002 could inhibit C‐fiber sensory neurological pathway‐related neurotransmitters 12, 13. The other is that the cold stress‐induced detrusor overactivity is associated with activation of C‐fiber sensory nerves 5.…”
Section: Discussionmentioning
confidence: 99%
“…THC‐002 (HARNCARE®) is a galenical produced from the traditional Chinese herbal mixture, Ba‐Wei‐Die‐Huang‐Wan (Hachimi‐jio‐gan). Previously, we showed that THC‐002 mitigates the C‐fiber sensory neurological pathway‐related detrusor overactivity,12 and it inhibits expression of urethral tachykinins13 in spontaneously hypertensive rats. THC‐002 also improves lower urinary tract functions in LUTS patients 14, 15.…”
Section: Introductionmentioning
confidence: 95%
“…c,d) and mRNA expression levels within the skin of THC‐002‐treated rats were significantly lower than that of control rats . THC‐002 and Goshajinkigan both mitigated the C‐fiber sensory nerve pathway‐related detrusor overactivity by decreasing the tachykinin neurotransmitters and/or receptors related to C‐fiber activation in the urinary bladder and urethra . In future studies, we will investigate the mechanism(s) of increased skin temperature and decreased TRPM8 expression levels within the skin by administration of THC‐002.…”
Section: Resistance To the Cold Stress Responses Provided By Traditiomentioning
confidence: 97%